Nutrimental concentration in ‘Hass’ avocado leaves with mottled symptom - Hernández-Valdés Edgardo Federico; Aguilar-Campoverde, Salvador; Aguiera-Taylor Verónica; Pérez-Sánchez Rosa Elena (Revista Mexicana de Ciencias Agrícolas, 2018)
The problem called as “mottled leaves” in avocado crop is widely spread in the most important production zones from Mexico, and it is unknown which factors are involved in this foliar symptom appearance. By this reason, the nutrimental content in ‘Hass’ avocado foils collected from trees without mottled presence (treatment A) was collated against leaves that either showed the symptom although coming from trees with foliar damage (treatment b) and leaves with symptom presence (Treatment C). It was found that those leaves with interveinal “mottled” had least N, P, K, and Mn concentration with regards the ones that show no symptom, while Ca, Mg, Fe, Zn, Cu and B concentrations in leaves with and without mottling were similar.